OPTIMALISASI KUALITAS LAYANAN PUBLIK DIGITAL BERBASIS E-GOVERNMENT MELALUI PENGUATAN KAPASITAS APARATUR KELURAHAN DI KOTA BAUBAU - Farid Yusuf Nur Achmad; Kiki Silvia Salam; Putri Mawang Sari (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The implementation of digital public services at the urban village level requires continuous capacity strengthening to ensure transparency, responsiveness, and service quality. This community service aimed to optimize the quality of e-government-based digital public services through strengthening the capacity of urban village officials in Baubau City. The program employed participatory approaches, including initial service mapping, capacity-building workshops, development of a digital service optimization model, and implementation assistance using practical monitoring tools. The results indicated increased understanding of digital governance principles, improved management of public information media, and enhanced responsiveness of online services. The developed optimization model provides a practical framework that can be adapted by local governments to improve digital service performance sustainably. This activity contributes to strengthening smart governance practices at the local government level.